A five years retrospective analytic study of maternal deaths at tertiary care centre, Gujarat, India - Patel, Manthan; Goswami, Kamal; Prajapati, Shetal; Chavda, Dolly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal mortality is one of the major challenges which face the developing countries throughout the world. The aim of the study is to assess the causes of maternal mortality at P.D.U. Medical College, and to identify the avoidable ones. Methods: Data were collected from records of patients who presented to and/or delivered at P.D.U. Medical College between 2011 and 2015. Only cases of maternal mortality were included in this study. In our study, we found 120 maternal deaths at our hospital between 2011 and 2015. Results: We found that the indirect causes of maternal mortality accounted for 29.3% of all mortalities. The leading cause of death in the 5 years was uncontrollable postpartum haemorrhage (23.3%), preeclampsia with its complications (15.8%), Anemia (14.1%), Abruption placentae 12.5% and Septicaemia 5% .Direct maternal deaths accounted for 70.7%. Conclusions: Preeclampsia and PPH, as well as their complications are the leading causes of death in one of the biggest tertiary care university hospitals in Egypt. However, there are other important avoidable predisposing factors that should be dealt with including lack of patient education, delayed transfer from other hospitals, and substandard practice.